2021
DOI: 10.2474/trol.16.210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Degree of Unsaturation in Vegetable Oils on Friction Properties of DLC Coatings

Abstract: Recently, it has been reported that combinations of various types of vegetable oils containing organic acids and DLC coatings are effective for reducing friction, but there are few reports of detailed investigations into the relationship between differences in the chemical structures of vegetable oil lubricants and friction reduction. Therefore, the authors investigated the influence on friction properties of two types of DLC coatings, a-C:H and ta-C under lubrication with vegetable oils which have different d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Along with the severe removal of carbon-based tribofilm from CPCa, the tribotest of this combination resulted in a continuous increase in the frictional outcome and an unstable antiwear performance. Adapting to the modern trends of low-viscosity lubricant development where the phosphorus and sulphur compounds are minimized [29], the DLC coatings were been studied to optimize their interactions with other "green" additives like Glycerol Mono-Oleate [159][160][161], fatty acid [162][163][164][165], etc. Noticeably, ultralow-friction outcomes originating from organic molecules and DLC coating interaction can be achieved by probing their hydroxyl-terminated tribolayers [166,167].…”
Section: Compatibility Of Carbon Tribofilms With Other Lubricant Addi...mentioning
confidence: 99%
“…Along with the severe removal of carbon-based tribofilm from CPCa, the tribotest of this combination resulted in a continuous increase in the frictional outcome and an unstable antiwear performance. Adapting to the modern trends of low-viscosity lubricant development where the phosphorus and sulphur compounds are minimized [29], the DLC coatings were been studied to optimize their interactions with other "green" additives like Glycerol Mono-Oleate [159][160][161], fatty acid [162][163][164][165], etc. Noticeably, ultralow-friction outcomes originating from organic molecules and DLC coating interaction can be achieved by probing their hydroxyl-terminated tribolayers [166,167].…”
Section: Compatibility Of Carbon Tribofilms With Other Lubricant Addi...mentioning
confidence: 99%
“…It has also been shown that the effect of increased unsaturation on tribological properties is more pronounced at higher temperatures [112]. Yoshida et al [111] also investigated the effect of double bonds on the COF of six vegetable oils with different levels of unsaturation in relation to the presence of mono-, di-, and tri-unsaturated FA. The oil with the highest content (%) of triunsaturation showed the highest COF results (linseed oil), followed by the oils with the highest content (%) of monounsaturation (rapeseed and olive oils).…”
Section: Tribological Characterization and Performance Of Vegetable-d...mentioning
confidence: 99%